Research on efficient impurity removal via chlorination roasting-acid leaching of low-grade molybdenum concentrate - Dehao Dou; Huan Tian; Tu Hu; Baocheng Zhou; Guo Lin; Libo Zhang; Jianwei Song; Junkui Shi; Yanfen Yang (Minerals Engineering, 2026)

Mechanisms of taVNS-induced working memory enhancement: a multimodal fNIRS–HRV–MEP study - Menghuan Wang; Wewei Dou; Xiang Gong; Yunjie Gui; Feng Lin; Dandan Liang (Cognitive Neurodynamics, 2026)

Impact of in-hospital trauma team activation workflow on early treatment timelines and hospital outcomes in patients with severe multiple trauma: A single-center pre-post implementation study - Hui Song; Peinan Tu; Qingli Dou; Jianwen Ye; Jinle Lin; Zhongyi Huang (Next Research, 2026)

Global ammonia (NH3) retrieval from the FY-3F satellite hyperspectral infrared atmospheric sounder and performance assessment - Zhili Deng; Yapeng Wang; Minqiang Zhou; Ling Gao; Lin Chen; Xifeng Cao; Lingfeng Zhang; Yuhan Jiang; Haiyang Dou; Xingying Zhang (Atmospheric Environment, 2026)

Design and solution of a curvature-bridging trajectory for friction reduction in offshore ERD - Zijun Dou; Yongsheng Liu; Leichuan Tan; Lin Chai; Gansheng Yang (Ocean Engineering, 2026)

Spatial heterogeneity of soil infiltration affected by tree roots: Insights from in-situ double-ring infiltrometer tests and soil physicochemical analysis - Yunzhao Lin; Jianjia Lu; Gengming Yan; Hongqiang Dou; Yilong Wu; Hao Wang; Wenbin Jian (Engineering Geology, 2026)

3D phase-field modeling of limestone dissolution process induced by CO2 - Wenchao Dou; Mian Lin (Chemical Geology, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

Association between residential greenness exposure and excessive gestational weight gain: A dual-center birth cohort study - Xuejin Li; Yanshen Zhang; Yijun Liu; Xiuping Dou; Man He; Yao Huang; Yang Su; Bingying Zhang; Weidong Luo; Qingmei Lin; Yongjun Shi; Boyi Yang; et al. (Environmental Research, 2026)

Efficacy and Mechanisms of Combined Central-Peripheral Magnetic Stimulation on Prefrontal-Sensorimotor Cortex Connectivity in Post-Stroke Dysphagia after Supratentorial Stroke: A Randomized, Single-Blind, Parallel-Controlled Trial - Zirui Luo; Zhiying Zhu; Yujue Wang; Na Su; Yajing Xue; Wanqi Zhang; Wei Liao; Yaoyao You; Lin Ling; Mei Li; Junjie Liang; Zulin Dou; et al. (Translational Stroke Research, 2026)

Critical assessment of synthetic microbial community strategies in vinegar brewing: from design paradigms to industrialization bottlenecks - Shiyuan Lin; Yongjian Yu; Yuanyuan Zhu; Ke Wang; Zhen Yu; Yuqin Wang; Dong Han; Xuezhi Wu; Nan Zhang; Shuaiwei Dou; Yunsong Yang (Critical Reviews in Food Science and Nutrition, 2026)

The influence of perforation stimulation for natural gas hydrates reservoir on seafloor stability - Lin Yang; Qianyong Liang; Xuhui Zhang; Yudong Huang; Xuemin Wu; Xiaofeng Dou; Zhigang Wang (Ocean Engineering, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Dynamic Analysis of Ecological Health Status of the Small Watersheds in Central Shandong, China Based on Remote Sensing Ecological Index and PCA - Xiuqin Sun; Qianxun Chen; Guangzhou Yu; Weijie Zhong; Feiyong Chen; Keqin Liu; Fengke Dou; Geng Xu; Lin Wang; Jin Wang (Journal of the Indian Society of Remote Sensing, 2026)

Divergent response of vegetation structure to land-atmosphere droughts across aridity gradients in the Northern Hemisphere - Bingxin Ma; Longhui Li; Yue Zhang; Yueyue Dou; Lin Yu (Global and Planetary Change, 2026)

17β-Estradiol alleviates cognitive deficits by modulating fear memory reconsolidation in a PTSD rat model - Han Wang; Han Lin; Zilong Zhong; Baoying Jiang; Siyi Li; Jiahao Tang; Xiaoping Zhou; Guohui Zhu; Yang Liu; Wenhao Han; Jinhua Dou; Lin Sun (Psychopharmacology, 2026)

A staged calibration strategy for SWAN whitecapping term coefficients to improve significant wave height and mean wave period - Hong-Sheng Zhang; Jun-Lin Zhu; Peng-Bo Zheng; Xiao-Dou Huang (Ocean Engineering, 2026)

A comprehensive review on the mechanism, applicability and selection of chlorinating agents - Dehao Dou; Huan Tian; Tu Hu; Baocheng Zhou; Guo Lin; Libo Zhang; Jianwei Song; Junkui Shi; Yanfen Yang (Journal of Environmental Chemical Engineering, 2026)

Optimal scheduling of mixed conventional and modular autonomous bus fleets for sustainable urban transit - Xueping Dou; Ran Dong; Yuqi Lin; Tongfei Li (Journal of Cleaner Production, 2026)

A closed-loop multi-agent swarm framework for synergistic location-routing optimization in municipal solid waste collection system - Yili Liu; Zhihong Lin; Wangrui Dou; Yanzhao Hao (Journal of Environmental Management, 2026)

Corrigendum to “Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration”. [229 (2026) 118495/FRIN 118495] - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Adaptive strategies of halophytes to saline and freshwater drip irrigation: a focus on transcription factors and metabolic pathways - Haitao Dou; Qiao Xu; Tao Lin; Zewen Tong; Aishajiang Aili; Hailiang Xu (Plant Cell Reports, 2026)

High-resolution annual desertification mapping in northern China using a novel comprehensive desertification index and unsupervised algorithm - Yaqing Dou; Huaiqing Zhang; Hua Sun; Hui Lin; Yang Liu; Meng Zhang (Remote Sensing of Environment, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

Constructing Ce–O–C covalent-bridged S-scheme heterojunction via molten-salt transformation of Ce-MOF for photocatalytic overall H2O2 synthesis - Ziying Feng; Pengjia Li; Dou Yang; Jingyi Yu; Yunyun Gui; Shao-Chuan Li; Yuan Lin; Junhua Zou; Lijun Liu (Journal of Environmental Chemical Engineering, 2026)

Engineering the cathode: Key to unlocking the potential of potassium-ion batteries - Yu Dong; Ning Wang; Wang-mi Chen; Qi Zhou; Ming-xiao Li; Zhen-tao Cui; Jia-qi Hou; Wen-lin Ruan; Bei-dou Xi (Chemical Engineering Journal, 2026)

Modeling the vertical air temperature rise patterns of densely-built urban canyons under building anthropogenic heat via a scaled outdoor experiment - Lin Liu; Shen Wang; Jingjing Dou; Guanwen Chen; Jian Hang; Xia Yang (Building and Environment, 2026)

Hierarchical drivers and adaptive strategies of zooplankton to aquatic environment in anthropogenically modified cascade reservoir ecosystems - Jingyun Yin; Jihong Xia; Chuanbin Dou; Yue Wang; Qianqian Mao; Zhicheng Liu; Yuanshuo Lu; Tao Hu; Huijie Yang; Yifei Ren; Guofu Lin (Journal of Oceanology and Limnology, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Exploring the feasibility of multi-element fingerprinting with chemometrics for discriminating the geographical origins of asparagus and its risk assessment - Qiuhong Zhang; Min Li; Chuanhao Dou; Xiangliang Yan; Bing Wang; Huimin Zhang; Yongqiang Lin; Dantong Zhao (Food Chemistry, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

A new perspective on endometriosis: Integrating eQTL mendelian randomization with transcriptomics and single-cell data analyses - Sheng Dou; Yi Wei; Zongyun Lin; Hui Wu; Fenglian Yang; Xuechang Cen; Wenjing Lu; Haimei Qin; Rong Wang; Junli Wang (Functional & Integrative Genomics, 2025)
Endometriosis is caused by the migration of endometrial cells to locations outside the uterine lining. Despite the increasing prevalence of endometriosis, there has been limited research on genetic effects, and its molecular mechanisms remain unclear. This study aimed to investigate the mechanisms underlying the development of endometriosis and to identify new genetic targets for endometriosis by integrating data from gene chips, single-cell mapping, and genome-wide association study databases. Using the Gene Expression Omnibus database, we downloaded data on normal endometrium, eutopic endometrium, and ectopic lesion tissues to explore the differentially expressed genes (DEGs) between normal and eutopic endometrium, and between eutopic and ectopic endometrium. Assessment of the relationships between DEGs and endometriosis involved differential expression, expression quantitative trait loci (eQTL), and Mendelian randomization (MR) analyses. Two single-cell atlas datasets were then analyzed to explore the mechanisms underlying disease development and progression. Intersection of MR results with DEGs between normal and eutopic endometrium highlighted 28 candidate biomarker genes (17 upregulated and 11 downregulated). Similarly, we identified two additional candidate biomarker genes by intersecting the DEGs between eutopic and ectopic endometrium with MR results. Among these 30 candidates, further filtering using single-cell datasets revealed that the histamine N-methyltransferase ( HNMT ), coiled-coil domain containing 28 A ( CCDC28A ), fatty acid desaturase 1 ( FADS1 ) and mahogunin ring finger 1 ( MGRN1 ) genes were differentially expressed between the normal and eutopic groups, consistent with transcriptomic and MR results. Our findings suggested that eutopic endometrium exhibits epithelial-mesenchymal transition (EMT). Cell communication analysis focused on ciliated epithelial cells expressing CDH1 and KRT23 revealed that, in the eutopic endometrium, ciliated epithelial cells are strongly correlated and interact with natural killer cells, T cells, and B cells. We identified four novel biomarker genes and found evidence for EMT in the eutopic endometrium. The mechanism of endometriosis progression may be closely related to EMT and changes in the immune microenvironment triggered by damage to ciliated epithelial cells.

Investigation of cavitation control mechanism around bionic hydrofoil from multi-perspective vortex identification methods - Huancheng Xue; Peifeng Lin; Wei Dou; Zhilei Jin; Zuchao Zhu; Xiaojun Li (Ocean Engineering, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Actin–myosin complex dissociation initiates programmed cell death during cold storage of grass carp muscle - Xin Xiong; Huijuan Zhang; Lin Chen; Peipei Dou; Tianzhuo Huang; Shuai Zhuang; Yuqing Tan; Huawei Ma; Hui Hong; Yongkang Luo (Food Research International, 2025)

Analysis of the damage characteristics of the Mandalay Royal Palace struck by the 2025 Mw 7.7 Myanmar earthquake - Xuchuan Lin; Xiaoxiang Yuan; Wen Bai; Aixia Dou (Earthquake Engineering and Engineering Vibration, 2025)

Constructing a synthetic microbial community by analyzing the microorganisms responsible for the core flavor substances of Zhenjiang aromatic vinegar and their interaction - Yongjian Yu; Jiaxin Liu; Yuanyuan Zhu; Ke Wang; Yuqin Wang; Dong Han; Zhen Yu; Siyuan Cheng; Nan Zhang; Shuaiwei Dou; Shiyuan Lin; Ziyi Kang (Food Bioscience, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

Investigation of intermittent motion mechanisms in large landslides based on in-situ monitoring and microtremor survey - Jian Yang; Huiqi Zhang; Wenbin Jian; Lipeng Lin; Luis F. Robledo; Hao Wang; Hongqiang Dou (Engineering Geology, 2025)

Electrocatalytic upcycling of polylactic acid hydrolysate and simultaneous hydrogen production - Ping He; Jiang-nan Xu; Jia-yang Dou; Bing Xu; She-ying Dong; Ting-lin Huang; Jun-Jie Zhu (Chemical Engineering Journal, 2025)

Calcium forms influence soil organic carbon by mediating labile organic carbon fractions, carbon pool management indices and microbial communities in calcareous alkaline soils - Xiaolu Dou; Congzhi Zhang; Lin Chen; Qicong Wu; Guixiang Zhou; Donghao Ma; Zhanhui Zhao; Jiabao Zhang (Plant and Soil, 2025)

Genetic Diversity in Three Sinipercine Fishes Based on Mitochondrial D-Loop and COX1 Sequences - Minghui Lin; Xu-Fang Liang; Ke Lu; Ming Zeng; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi), golden mandarin fish (Siniperca scherzeri), and Coreoperca whiteheadi are three important aquaculture species in China facing several threats to their production. Genetic diversity was assessed by sequencing the mitochondrial D-loop and cox1 regions in 207 individuals across nine populations. The genetic diversity analysis, based on the concatenated sequences, revealed that the total haplotype diversity was high across all sinipercine fish populations. Population differentiation analysis revealed that most genetic variation was within populations: 74.5% in S. chuatsi (p

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Multi-omics joint analysis: Pachymic acid ameliorated non-alcoholic fatty liver disease by regulating gut microbiota - Guilin Ren; Yiyou Lin; Yilong Fu; Fucai Liu; Ruiqi Wang; Congcong Zhang; Jiannan Qiu; Lin Chen; Xiaobing Dou (Food Research International, 2025)

Electrostatic-Induced Crystal-Rearrangement of Benzoquinones Cathode for Large-Scale All-Organic Aqueous Proton Batteries - Jianyong Zhang; Jingyuan Yu; Wenwei Zhang; Ahmed Eissa Abdelmaoula; Chunhua Han; Zhenzhen Dou; Feng Liang; Lin Xu (Chemical Engineering Journal, 2025)

Island-like FeS2@TiO2 heterojunction modified separator for enhanced polysulfide management in lithium-sulfur batteries - Jing Song; Luchao Yue; Yifan Dou; Kun Yang; Lixin Zhang; Lin Jiang; Hongrui Liang; Yu Cao; Tianwei Fan; Xujie Zhang; Guisheng Qi; Xuping Sun; et al. (Chemical Engineering Journal, 2025)

Quantifying the impacts of climate change and human activities on vegetation in ecologically fragile regions: a case study of Northern China - Xiangzhou Dou; Xiumei Li; Guoqing Sang; Ping Yang; Yuhu Zhang; Jianing Wang; Zhicheng Zhong; Feng Lin; Qiang Zhao (Theoretical and Applied Climatology, 2025)

Degradation of the mechanical properties of root–soil composites under moisture influence - Yunzhao Lin; Wenbin Jian; Yilong Wu; Zuteng Zhu; Hao Wang; Hongqiang Dou; Xiufeng Fan (Bulletin of Engineering Geology and the Environment, 2025)

Efficient photocatalytic CO2 and Cr(VI) reduction on carbon quantum dots/carbon nitride heterojunctions - Zhengdong Xu; Xun Su; Penghui Yang; Junbo Zhong; Minjiao Li; Clemens Burda; Lin Dou (Fuel, 2025)

Overestimation of pore volume in high-TOC shales by low-temperature nitrogen adsorption: Phenomenon and cause analysis - Wenbin Jiang; Di Zhu; Chao Luo; Gaohui Cao; Lili Ji; Mian Lin; Zhuo Chen; Wenchao Dou; Kesu Zhong; Zhanhe Jia; Fang Hao (Chemical Engineering Journal, 2025)

Treadmill Exercise Enhances Post-Stroke Functional Recovery in Mice via the CX3CL1/CX3CR1 Signaling Pathway - Yangyang Ge; Xiaoke Dou; Pu Chen; Jiayi Chen; Maosha Dai; Shanglong Yao; Yun Lin (Molecular Neurobiology, 2025)

Egg production monitoring in commercial laying cages via the StrongSort-EGG tracking-by-detection model - Rui Wu; Pengguang He; Yefan He; Jun Dou; Mengzui Di; Shupeng He; Khawar Hayat; Yi Zhou; Lin Yu; Jinming Pan; Hongjian Lin (Computers and Electronics in Agriculture, 2024)

Relationship between calcium forms and organic carbon content in aggregates of calcareous soils in northern China - Xiaolu Dou; Congzhi Zhang; Jiabao Zhang; Donghao Ma; Lin Chen; Guixiang Zhou; Yan Duan; Lu Tao; Junxu Chen (Soil and Tillage Research, 2024)

Investigating dehumidification and heating performance in a dual evaporator heat pump system for electric vehicles - Kang Li; Mingfei Tan; Yuan Man; Hua Zhang; Binlin Dou; Ni Liu; Tianjiao Zhang; Qize He; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

Refined one-dimensional modeling and experimental validation of scroll compressor with vapor injection for electric vehicles - Kang Li; Jiayun Hu; Chao Li; Xuejin Zhou; Ni Liu; Hua Zhang; Binlin Dou; Qize He; Ran Tu; Lin Su; Soheil Mohtaram (International Journal of Refrigeration, 2024)

In-situ infiltration-runoff characterization of slopes under the influences of different rainfall patterns and slope gradients - Ruimin Chen; Hongqiang Dou; Yunzhao Lin; Qingling Liu; Wenbin Jian (CATENA, 2024)

Effects of dietary arginine supplementation on muscle structure, meat characteristics and lipid oxidation products in lambs and its potential mechanisms of action - Lu Dou; Chang Liu; Rina Su; Mirco Corazzin; Zhimin Jin; Zhihao Yang; Guanhua Hu; Min Zhang; Lina Sun; Lihua Zhao; Ye Jin; Lin Su (Meat Science, 2024)

Molecular mechanism of saturated aldehyde oxidation: A DFT insight into volatiles forming from decanal thermal oxidation - Binchen Wang; Shaohua Dou; Shang Wang; Yi Wang; Sufang Zhang; Xinping Lin; Chaofan Ji; Liang Dong (Food Chemistry, 2024)

Caspase-3 interactions with calpain and cathepsin L: Implications for protein stability and quality in fish fillets during postmortem storage - Xiong Xin; Ding Ning; Zhuang Shuai; Dou Peipei; Feng Ruifang; Tan Yuqing; Ma Huawei; Chen Lin; Hong Hui; Luo Yongkang (Food Bioscience, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Metal-organic cages for efficient capture and convenient detection of iodine from vapor and aqueous solutions - Zhi-Yong Zeng; Zhen-Chen Lou; Lianrui Hu; Weitao Dou; Xiaoli Zhao; Xiaodong Li; Junfeng Fang; Xuhong Qian; Hai-Bo Yang; Lin Xu (Chemical Engineering Journal, 2024)

Climatic and anthropogenic forcing of vegetation change at different altitudes on the northeastern Tibetan Plateau over the past millennium - Dou Chen; Youmo Li; Shilong Guo; Tao Wang; Lin Chen; Lanlan Hu; Jinghua Huang; Lili Pan; Xuyi Ma; Duo Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Green synthesis of azo-linked porous organic polymer for enrichment of nitroimidazoles from water, shrimp and Basa fish - Yiran Dou; Cong Liu; Xiaocui Chen; Xiumin Yang; Lin Hao; Qianqian Wang; Zhi Wang; Qiuhua Wu; Chun Wang (Food Chemistry, 2024)

Effect of sheep bone protein hydrolysate on promoting calcium absorption and enhancing bone quality in low-calcium diet fed rats - Guanhua Hu; Xueying Sun; Shiqi Hao; Xiaotong Li; Min Qian; Lu Dou; Min Zhang; Puxin Hou; Lin Su; Lihua Zhao; Lina Sun; Ye Jin (Food Chemistry, 2024)

Structure parameter as an intrinsic property of thin-film composite forward osmosis membrane - Shuwei Zhao; Nan Sun; Pengjia Dou; Saisai Lin; Tao He (Desalination, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Association of NID2 SNPs with Glioma Risk and Prognosis in the Chinese Population - Jie Hao; Congmei Huang; Weiwei Zhao; Lin Zhao; Xiuxia Hu; WenJie Zhang; Le Guo; Xia Dou; Tianbo Jin; Mingjun Hu (NeuroMolecular Medicine, 2024)

Strong opioids-induced cardiac, neurologic, and respiratory disorders: a real-world study from 2004 to 2023 based on FAERS - Maosha Dai; Xiaoke Dou; Min Chen; Juexi Yang; Junhao Long; Yun Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

On the Shallowing of Antarctic Low-Level Temperature Inversions Projected by CESM-LE under RCP8.5 - Minghu Ding; Lin Zhang; Tingfeng Dou; Yi Huang; Yingyan Luo; Junmei Lyu; Cunde Xiao (Journal of Meteorological Research, 2024)

Effects of cache distribution and size on cache foraging by animals - Ling Hou; Haojun Dou; Mingjie Hu; Lin Cao (Animal Behaviour, 2024)

Effects of exercise on muscle fiber conversion, muscle development and meat quality of Sunit sheep - Lin Su; Congying Zhao; Bing Sun; Lu Dou; Chenlei Wang; Zhihao Yang; Tianle Li; Ye Jin (Meat Science, 2024)

Self-healing, environmentally stable and adhesive hydrogel sensor with conductive cellulose nanocrystals for motion monitoring and character recognition - Yafang Wang; Anrong Yao; Baojie Dou; Cuimin Huang; Lin Yang; Juan Liang; Jianwu Lan; Shaojian Lin (Carbohydrate Polymers, 2024)

Optimal selection of inversion method for gas-adsorption pore characterization of shales in Wufeng and Longmaxi Formation, Sichuan Basin - Wenbin Jiang; Mian Lin; Chao Luo; Zhuo Chen; Gaohui Cao; Lili Ji; Wenchao Dou; Kesu Zhong; Fang Hao (Chemical Engineering Journal, 2024)

Unraveling proteome changes of Sunit lamb meat in different feeding regimes and its relationship to flavor analyzed by TMT-labeled quantitative proteomic - Zhihao Yang; Yanru Hou; Min Zhang; Puxin Hou; Chang Liu; Lu Dou; Xiaoyu Chen; Lihua Zhao; Lin Su; Ye Jin (Food Chemistry, 2024)

Importance of diagenetic heterogeneity in Chang 7 sandstones for modeling CO2-water-rock interactions - Wenchao Dou; Mian Lin; Wenbin Jiang; Lili Ji; Gaohui Cao (International Journal of Greenhouse Gas Control, 2024)

Directional guiding of mass and charge transfer via vertically aligned graphite nanosheets for high-rate and ultralong lifespan Dual-ion batteries - Lin Shang; Bi-Yun Shi; Xianchun Liu; Tian-Tian Zhang; Hanlin Liu; Yongping Zheng; Wei-Dong Dou; Qingguang Pan; Yongbing Tang (Chemical Engineering Journal, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Spatial patterns of light response parameters and their regulation on gross primary productivity in China - Yong Lin; Zhi Chen; Guirui Yu; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Wenxing Luo (Agricultural and Forest Meteorology, 2024)

Widely targeted metabolomic analysis reveals the dynamic changes of metabolites during postmortem chilled aging in Mongolian sheep - Min Zhang; Lina Sun; Rina Su; Mirco Corazzin; Zhihao Yang; Lu Dou; Guanhua Hu; Yue Zhang; Ting Liu; Yueying Guo; Lihua Zhao; Lin Su; et al. (Food Chemistry, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Observation of Arctic surface currents using data from a surface drifting buoy - Hongxia Chen; Lina Lin; Long Fan; Wangxiao Yang; Yinke Dou; Bingrui Li; Yan He; Bin Kong; Guangyu Zuo; Na Liu (Acta Oceanologica Sinica, 2024)

The effect of chlorite rims on reservoir quality in Chang 7 sandstone reservoirs in the Ordos Basin, China - Wenchao Dou; Mian Lin; Luofu Liu; Langbo Jia (Marine and Petroleum Geology, 2023)

Fabrication of graphene-rapped melamine sponge and its photothermal adsorption on viscous oil spill - Huie Liu; Zimei Lin; Shi Guo; Qilin Guo; Shuang Chen; Xiangyan Dou (Journal of Environmental Chemical Engineering, 2023)

Molten salt-assisted carbonized zeolite imidazolate framework on nickel foam for highly efficient iodide capture in fluoride molten salts - Ming Cheng; Junxia Geng; Yujiao Wang; Qin Lin; Xiaoyu Zhang; Lixin Sun; Qiang Dou; Haiying Fu (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Effect of dietary arginine supplementation on protein synthesis, meat quality and flavor in growing lambs - Lu Dou; Lina Sun; Chang Liu; Lin Su; Xiaoyu Chen; Zhihao Yang; Guanhua Hu; Min Zhang; Lihua Zhao; Ye Jin (Meat Science, 2023)

Supplemental Clostridium butyricum modulates skeletal muscle development and meat quality by shaping the gut microbiota of lambs - Lu Dou; Chang Liu; Xiaoyu Chen; Zhihao Yang; Guanhua Hu; Min Zhang; Lina Sun; Lin Su; Lihua Zhao; Ye Jin (Meat Science, 2023)

Design and development of a new lead-free BiFeO3-BaTiO3 quenched ceramics for high piezoelectric strain performance - Muhammad Habib; Lin Tang; Guoliang Xue; Attaur Rahman; Myong-Ho Kim; Soonil Lee; Xuefan Zhou; Yan Zhang; Dou Zhang (Chemical Engineering Journal, 2023)

Calcium carbonate regulates soil organic carbon accumulation by mediating microbial communities in northern China - Xiaolu Dou; Jiabao Zhang; Congzhi Zhang; Donghao Ma; Lin Chen; Guixiang Zhou; Jingwang Li; Yan Duan (CATENA, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Distribution-based maximum likelihood estimation methods are preferred for estimating Salmonella concentration in chicken when contamination data are highly left-censored - Tianmei Sun; Yangtai Liu; Shufei Gao; Xiaojie Qin; Zijie Lin; Xin Dou; Xiang Wang; Hui Zhang; Qingli Dong (Food Microbiology, 2023)

The influences of the oil circulation ratio on the performance of a vapor injection scroll compressor in heat pump air conditioning system intended for electrical vehicles - Kang Li; Jingru Ma; Jian Cao; Bin Zhang; Binlin Dou; Ni Liu; Hua Zhang; Lin Su; Xuejin Zhou; Ran Tu (International Journal of Refrigeration, 2023)

Pexidartinib hydrochloride exposure induces developmental toxicity and immunotoxicity in zebrafish embryos via activation of Wnt signaling - Fasheng Liu; Hongmei Hu; Guilan Chen; Yanqi Lin; Wei Li; Ziyi Liu; Chao Chen; Xue Li; Sujie Sun; Li Zhang; Dou Yang; Kangyu Liu; et al. (Fish & Shellfish Immunology, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

High electric field-induced ferroelectric loss of polymer/paraelectric barium titanate particle nanocomposites - Elshad Allahyarov; Qiong Li; Tianxiong Ju; Yeu-Wei Harn; Hang Luo; Dou Zhang; Zhiqun Lin; Lei Zhu (Chemical Engineering Journal, 2023)

Dietary L-arginine supplementation influences the muscle fiber characteristics and meat quality of Mongolian sheep through the NO/AMPK/PGC-1α pathway - Lina Sun; Liyuan Xu; Lihua Zhao; Lu Dou; Yanru Hou; Chenlei Wang; Ye Jin; Lin Su (Food Bioscience, 2023)

Do tillage systems affect the cadmium threshold in farmland soil for environmental quality standard setting? - Zhaolin Du; Weiqiang Dou; Dasong Lin; Li Qin; Yi An; Hongan Chen; Lina Wu; Liyan Mou (Science of The Total Environment, 2023)

Lipid transformation during postmortem chilled aging in Mongolian sheep using lipidomics - Min Zhang; Rina Su; Mirco Corazzin; Ran Hou; Yue Zhang; Lina Sun; Guanhua Hu; Lu Dou; Yueying Guo; Lin Su; Lihua Zhao; Ye Jin (Food Chemistry, 2023)

Comparing the structural characteristics and expression of GA2ox gene in dwarf banana and its wild type - Jiaqi Lin; Dou Feng; Yanpei Li; Shixiang Xiao; Weiyan Xuan (Journal of Plant Biochemistry and Biotechnology, 2023)
It is necessary to understand the molecular mechanism of banana dwarfing mutation in order to improve the high stem character of banana varieties and breed the new excellent dwarf lines. To elucidate the molecular-level regulation of banana dwarf mutations and identify the relevant genes, the complete cDNA sequence of the gibberellin 2-oxidase gene ( GA2ox ) in the dwarf banana and its wild type was cloned by RT-PCR and the encoded amino acid sequences bioinformatically was analyzed. Meanwhile, the expression levels of banana GA2ox gene in different tissues of dwarfed banana and its wild type were analyzed by qRT-PCR. Between the GA2ox gene sequences of the dwarf banana and its wildtype, there were 5 base pairs of variation, leading to the predicted GA2ox proteins having different molecular weights, isoelectric points, fat indices, total numbers of positive and negative charges, and hydrophilicity. In addition, the expression of GA2ox in the leaves, stalks, and fruits of dwarf banana plants was higher than that in the wild type in the early and middle stages of banana development. The results showed that the GA2ox gene may have important regulatory effects on banana stem dwarfing, the knowledge of which can help our understanding and manipulation of this important plant.

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

Sputter-deposited nickel nanoparticles on Kevlar fabrics with laser-induced graphene for efficient solar evaporation - Shuaihang Zhu; Zhiwei Lei; Yuejie Dou; Ching-Wen Lou; Jia-Horng Lin; Jiwei Li (Chemical Engineering Journal, 2023)

A case study of offshore wind turbine positioning optimization methodology using a novel multi-stage approach - Xiaosen Xu; Lin Du; Zhongyu Zhang; Jiayang Gu; Yihan Xing; Oleg Gaidai; Peng Dou (Frontiers in Marine Science, 2022)
This investigation maximize the annual energy production (AEP) of a wind farm’s layout at a specific site using a novel multi-stage approach. The downstream wind turbines’ energy production decreases due to the reduced wind speed and turbulence created by the upstream wind turbines’ wakes. The wake interference from wind turbines causes the reduction of overall power efficiency. This paper provides a novel multi-stage strategy for the optimal layouts generated by heuristic algorithms to address this problem. A comparison of the proposed multi-stage approach to previous optimization algorithms is presented to demonstrate its efficiency using three referenced cases and one potential wind farm in the Gulf of Maine. The results demonstrate that applying the proposed multi-stage approach increases AEP and decreases computational time compared to previous research and optimization algorithms, which is crucial for large-scale offshore wind farm layout design and optimization.

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

Phylogeographic structure and population demography of the leopard mandarin fish (Siniperca scherzeri) in the Pearl River drainage - Minghui Lin; Xufang Liang; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Environmental Biology of Fishes, 2022)

MicroRNA-9 facilitates hypoxia-induced injury and apoptosis in H9c2 cells via targeting CDK8 - Pengcheng Dou; Guangshuang Tan; Zhihua Fan; Jiatong Xiao; Chaoran Shi; Zhengjun Lin; Juan Duan (Journal of Biosciences, 2021)

Human Methylmercury Exposure and Potential Impacts in Central Tibet: Food and Traditional Tibetan Medicine - Menghan Cheng; Maodian Liu; Dou Li; Qing Luo; Zhihao Zhang; Liuliang Yuan; Chenghao Yu; Han Xie; Huiming Lin; Qianru Zhang; De Ji; Xuejun Wang (Bulletin of Environmental Contamination and Toxicology, 2021)

Epididymal initial segment-specific Cre recombinase activity in Lcn8-Cre knock-in mice - Qian-qian Gong; Zhi-lin Dou; Xiao Wang; Ke-yi Zhang; Hao Chen; Jian-gang Gao; Xiao-yang Sun (Molecular Biology Reports, 2021)

Upregulated SOCC and IP3R calcium channels and subsequent elevated cytoplasmic calcium signaling promote nonalcoholic fatty liver disease by inhibiting autophagy - Lin Zhang; Yifan Zhang; Yuanqing Jiang; Xiaobing Dou; Songtao Li; Hui Chai; Qianyu Qian; Miaojuan Wang (Molecular and Cellular Biochemistry, 2021)

The mechanism and application of high-pressure water jet technology to prevent compound dynamic disaster - Zeng-qiang Yang; Chang Liu; Feng-shuo Li; Lin-ming Dou; Gang-wei Li; Da-wei Wang (Arabian Journal of Geosciences, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

The resurgent landscape of xenotransplantation of pig organs in nonhuman primates - Xuan Zhang; Quancheng Wang; Jingjun Zhao; Xiao Li; Wei Peng; Zhaoxu Yang; Zhibin Lin; Long Yang; Rui Ding; Kaishan Tao; Kefeng Dou (Science China Life Sciences, 2021)

The TOR pathway participates in the regulation of growth development in juvenile spotted drum (Nibea diacanthus) under different dietary hydroxyproline supplementation - Hua Rong; Fan Lin; Yunlong Zhang; Baoliang Bi; Tengfei Dou; Xiangwei Wu; Jude Juventus Aweya; Xiaobo Wen (Fish Physiology and Biochemistry, 2020)

Endoplasmic reticulum‐associated degradation mediated by MoHrd1 and MoDer1 is pivotal for appressorium development and pathogenicity of Magnaporthe oryzae - Wei Tang; Haolang Jiang; Osakina Aron; Min Wang; Xueyu Wang; Jiangfeng Chen; Birong Lin; Xuehang Chen; Qiaojia Zheng; Xiuqin Gao; Dou He; Airong Wang; et al. (Environmental Microbiology, 2020)
Summary Most secretory proteins are folded and modified in the endoplasmic reticulum (ER); however, protein folding is error‐prone, resulting in toxic protein aggregation and cause ER stress. Irreversibly misfolded proteins are subjected to ER‐associated degradation (ERAD), modified by ubiquitination, and degraded by the 26S proteasome. The yeast ERAD ubiquitin ligase Hrd1p and multispanning membrane protein Der1p are involved in ubiquitination and transportation of the folding‐defective proteins. Here, we performed functional characterization of MoHrd1 and MoDer1 and revealed that both of them are localized to the ER and are pivotal for ERAD substrate degradation and the ER stress response. MoHrd1 and MoDer1 are involved in hyphal growth, asexual reproduction, infection‐related morphogenesis, protein secretion and pathogenicity of M. oryzae . Importantly, MoHrd1 and MoDer1 mediated conidial autophagic cell death and subsequent septin ring assembly at the appressorium pore, leading to abnormal appressorium development and loss of pathogenicity. In addition, deletion of MoHrd1 and MoDer1 activated the basal unfolded protein response (UPR) and autophagy, suggesting that crosstalk between ERAD and two other closely related mechanisms in ER quality control system (UPR and autophagy) governs the ER stress response. Our study indicates the importance of ERAD function in fungal development and pathogenesis of M. oryzae .

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Nitrogen fertilizer enhances zinc and cadmium uptake by hyperaccumulator Sedum alfredii Hance - Ziwen Lin; Chunying Dou; Yongfu Li; Hailong Wang; Nabeel Khan Niazi; Shaobo Zhang; Dan Liu; Keli Zhao; Weijun Fu; Yongchun Li; Zhengqian Ye (Journal of Soils and Sediments, 2020)

Effects of Short Term Methylmercury Exposure on Growth and Development of the Large Yellow Croaker Embryos and Larvae - Xiang Yu; Fangzhu Wu; Xiaoqun Xu; Quanzhen Chen; Lin Huang; Berhane Teklehaimanot Tesfai; Liang Cao; Xudan Xu; Shuozeng Dou; Wei Huang (Frontiers in Marine Science, 2019)

Study on Properties of Grouting Materials and Reinforcement Effect in Coal Roadways Influenced by Dynamic Pressure - Zeng-qiang Yang; Chang Liu; Yun Dong; Lin-ming Dou; Jing-ke Wu (Geotechnical and Geological Engineering, 2019)

Rockburst occurrences and microseismicity in a longwall panel experiencing frequent rockbursts - Zhen-lei Li; Xue-qiu He; Lin-ming Dou; Gui-feng Wang (Geosciences Journal, 2018)

Resisting impact mechanical analysis of an anchored roadway supporting structure under P-wave loading and its application in rock burst prevention - Zheng-yi Wang; Lin-ming Dou; Gui-feng Wang; Long-fei Feng; Kai Kang; Jin-zheng Bai; Sheng-chuan Wang (Arabian Journal of Geosciences, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Sorting nexin (MoVps17) is required for fungal development and plant infection by regulating endosome dynamics in the rice blast fungus - Huawei Zheng; Zhongkun Guo; Yang Xi; Mingyue Yuan; Yahong Lin; Congxian Wu; Yakubu Saddeeq Abubakar; Xianying Dou; Guangpu Li; Zonghua Wang; Wenhui Zheng; Jie Zhou (Environmental Microbiology, 2017)
Summary Vps17 is a sorting nexin (SNX) and a component of the retromer, a protein complex mediating retrograde vesicle transport between endosomes and the trans‐Golgi network. However, its role in the development and pathogenicity of filamentous fungi such as the rice blast fungus ( Magnaporthe oryzae ) remains unclear. We investigate the functional relationship between the SNX and the cargo‐selective complex (CSC) of the fungal retromer by genetic analysis, live cell imaging and immunological assay. Our data show that the MoVps17 null mutation causes defects in growth, development and pathogenicity in M. oryzae . MoVps17 is localized to endosomes depending on the activity of phosphatidylinositol 3‐kinase (PI3K), a key enzyme for fungal development and infection. Both PX and BAR domains of MoVps17 are essential for its endosomal localization and function. Furthermore, our yeast two‐hybrid assays show that MoVps17 and MoVps5 can interact. Lastly, live cell imaging suggests that MoVps17 can regulate early endosome fusion and budding as well as endocytosis. Taken together, our results suggest that MoVps17 specifically functions as a retromer component with CSC and also plays a distinct role in the regulation of endosome dynamics during fungal development and plant infection.

Rock burst assessment in multi-seam mining: a case study - Wei Shen; Lin-ming Dou; Hu He; Guang-an Zhu (Arabian Journal of Geosciences, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

Microseismic Precursory Characteristics of Rock Burst Hazard in Mining Areas Near a Large Residual Coal Pillar: A Case Study from Xuzhuang Coal Mine, Xuzhou, China - An-ye Cao; Lin-ming Dou; Chang-bin Wang; Xiao-xiao Yao; Jing-yuan Dong; Yu Gu (Rock Mechanics and Rock Engineering, 2016)

Evolution of Stress Concentration and Energy Release Before Rock Bursts: Two Case Studies from Xingan Coal mine, Hegang, China - Gui-feng Wang; Si-yuan Gong; Zhen-lei Li; Lin-ming Dou; Wu Cai; Yong Mao (Rock Mechanics and Rock Engineering, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

The substrate promiscuity of a phosphopantetheinyl transferase SchPPT for coenzyme A derivatives and acyl carrier proteins - Yue-Yue Wang; Hong-Dou Luo; Xiao-Sheng Zhang; Tao Lin; Hui Jiang; Yong-Quan Li (Archives of Microbiology, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Characterisation of oligosaccharides from Baizhu by HILIC-MS - Zhe Lin; Yan-Fang Liu; Yang Qu; Li-Ying Shi; De-Qiang Dou; Hai-Xue Kuang (Natural Product Research, 2015)

Potential influence of the November–December Southern Hemisphere annular mode on the East Asian winter precipitation: a new mechanism - Zhiwei Wu; Juan Dou; Hai Lin (Climate Dynamics, 2015)

Microseismic and acoustic emission effect on gas outburst hazard triggered by shock wave: a case study - Cai-Ping Lu; Lin-Ming Dou; Nong Zhang; Jun-Hua Xue; Guang-Jian Liu (Natural Hazards, 2014)

NADPH oxidase 2 plays a critical role in dysfunction and apoptosis of pancreatic β-cells induced by very low-density lipoprotein - Juan Jiao; Lin Dou; Miao Li; Yonggang Lu; Han-Bang Guo; Yong Man; Shu Wang; Jian Li (Molecular and Cellular Biochemistry, 2012)

Arbuscular mycorrhiza regulate inter-specific competition between a poisonous plant, Ligularia virgaurea, and a co-existing grazing grass, Elymus nutans, in Tibetan Plateau Alpine meadow ecosystem - Liang Jin; Guiqi Zhang; Xiaojuan Wang; Cunyan Dou; Mu Chen; Shuangshuang Lin; Yuanyuan Li (Symbiosis, 2011)

Toxicity Testing of Waterborne Mercury with Red Sea Bream (Pagrus major) Embryos and Larvae - Wei Huang; Liang Cao; Xiujuan Shan; Longshan Lin; Shuozeng Dou (Bulletin of Environmental Contamination and Toxicology, 2011)

Statistical Assessment of the Impact of Conservation Measures on Streamflow Responses in a Watershed of the Loess Plateau, China - Lin Dou; Mingbin Huang; Yang Hong (Water Resources Management, 2009)